Akurasi Altman Z-Score Dalam Memprediksi Potensi Kebangkrutan Emiten Sektor Restoran, Hotel Dan Pariwisata Pada Masa Pandemi Covid-19 - Fridayana Yudiaatmaja; Trianasari; Ni Made Suci; Rahutama Atidira (Jurnal Ilmiah Akuntansi dan Humanika, 2023)
The purpose of this study was to determine the accuracy of the Altman Z-Score in predicting the potential for bankruptcy of public sector companies, hotels and tourism. This study used a quantitative descriptive research design because the data used are quantitative data and the bankruptcy variable described using the Altman Z-Score method. The data used are secondary data derived from the financial statements of issuers in the tourism, restaurant and hotel sectors including data on working capital to total assets, retained earnings to total assets, earnings before interest and taxes to total assets, and total equity to total debt. . The results showed that 19% of companies that experienced losses in 2021, the remaining 81% of companies experienced losses. The results of the classification comparison based on the Z-Score value and the auditor's opinion show that 43% was accurate, while the remaining 57% was inaccurate.